If it's not what You are looking for type in the equation solver your own equation and let us solve it.
1=(3+k)/9
We move all terms to the left:
1-((3+k)/9)=0
We add all the numbers together, and all the variables
-((k+3)/9)+1=0
We multiply all the terms by the denominator
-((k+3)+1*9)=0
We calculate terms in parentheses: -((k+3)+1*9), so:We get rid of parentheses
(k+3)+1*9
We add all the numbers together, and all the variables
(k+3)+9
We get rid of parentheses
k+3+9
We add all the numbers together, and all the variables
k+12
Back to the equation:
-(k+12)
-k-12=0
We add all the numbers together, and all the variables
-1k-12=0
We move all terms containing k to the left, all other terms to the right
-k=12
k=12/-1
k=-12
| 5x/8=4 | | 1=-3+k/9 | | 2/3x+4/5=1/6x+3/10 | | -2=n/5-5 | | 13n−4=43−13n | | 1/4x+1/2=1/5x+3/5 | | -6.85+4m=-11 | | 5v+7=42 | | -98=-2x-7(x+5) | | 0.4x-0.7=0.2+0.3 | | 43/10-(12/5x+11/2)=1/2(-15/5x+6/5) | | -v-1=17 | | -p+4=-5 | | 0.5x+1.1=0.25+1.6 | | e/8+9=21 | | 7(p+6)=21 | | 17w=-15 | | 180=8x+16+6x-60 | | 3m×.75=6.25 | | 10-6x=4+5x | | 11x-33=5x+7 | | (3,-7)m=3.5 | | -6x+6=27 | | 11y+20=15y | | 0=16t^2+48t | | 2/5/x=2/0.4 | | 7z=3z+40 | | t+48=13t | | u+18=2u+14 | | 8x+74∘2x+56∘=180∘ | | 9s-36=5s+16 | | 13=2x-32 |